Analisis Kualitas Produk Brake Coupling Menggunakan Metode Seven Tools di PT. Pindad - Icha Apriviani; Randi Juniar Arif; Dede Lastri; Asfara Idla Oliya (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The Brake Coupling is a railway braking system component manufactured through metal casting at PT Pindad (Persero). During the January 2024–June 2025 production period, the product recorded an average defect rate of 0.745%, with 166 defective units out of 22,283 produced. This study aims to identify the dominant defect types, determine their root causes, and propose improvements using the Seven Quality Control Tools, including Check Sheets, Histograms, Pareto Charts, Flow Process Charts, p-Control Charts, and Fishbone Diagrams. The results show that visual defects account for 50.60% of total defects, followed by porosity (41.57%) and cracks (7.83%). Based on the Pareto principle, the two main defect types contribute 92.2% of all defects. The p-control chart indicates the process remains statistically controlled despite noticeable fluctuations. Improvement proposals include standardized work instructions, a molding sand moisture testing program, and reactivation of operator training.